Major antigenic differences in Aeromonas salmonicida isolates correlate with the emergence of a new strain causing furunculosis in Chilean salmon farms - Mancilla, Marcos; Ojeda, Adriana; Yuivar, Yassef; Grandón, Maritza; Grothusen, Horst; Oyarzún, Marcela; Bisquertt, Alejandro; Ugalde, Juan A.; Fuentes, Francisco; Ibarra, Pablo; Bustos, Patricio (Frontiers in Cellular and Infection Microbiology, 2025)
Aeromonas salmonicida is the etiological agent of furunculosis, a septicemic disease with high mortality rates affecting salmonids and other teleost species worldwide. Reviewing molecular diagnostic protocols for routine diagnostics, we realized that the amplification of the vapA target gene failed in some cases of furunculosis. Therefore, we hypothesized that the emergence of a new strain may be involved in recent outbreaks. In this work, we demonstrate that the vapA locus is absent in the new strain, which explains why it lacks the major membrane component VapA protein, a critical virulence factor. In addition, we found that the vapA-absent strain differs from its counterparts in outer membrane protein and lipopolysaccharide profiles, suggesting profound changes at the membrane structure level and in antigenic properties. These features along with sequence analysis information allowed us to infer that a complex genomic rearrangement, probably an indel encompassing the entire vapA locus, gave rise to this membrane phenotype. Although the causes for pathogen evolution and emergence were not fully elucidated, our results strongly suggest that the vapA-absent strain is responsible for a raising proportion of recent furunculosis cases, and that it may be related to a less virulent disease and a low serological response upon vaccination with the A. salmonicida antigen formulation currently used in Chile.